Enhanced Debye level in nano Zn1+xSb, FeSb2, and NiSb: Nuclear inelastic spectroscopy on121 Sb. Issue 5 (16th February 2014) - Claudio, Tania; Bessas, Dimitrios; Birke, Christina S.; Kieslich, Gregor; Panthöfer, Martin; Sergueev, Ilya; Tremel, Wolfgang; Hermann, Raphael P.
<x xml:space="preserve">Abstract</x> The121 Sb partial density of phonon states (DPS) in nanopowder antimonides were obtained with nuclear inelastic scattering on <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh5jt6md" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />Zn1+xSb</alternatives>, <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh5jt6pc" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />FeSb2</alternatives>, and NiSb prepared by a wet chemistry route. The DPS is compared with the bulk counterpart. An increase of the Debye level indicative of a decrease of the isothermal speed of sound is systematically observed. This observation reveals that the decrease in speed of sound observed in nanostructured thermoelectric materials is not restricted to sintered nanocomposites.